Methodology for the design and control of flexible manufacturing cells. (24th June 2005) - Luis, C.; Blanco, J.; Sebastian, M.
The design of a flexible manufacturing system involves a complex process in which it is necessary to take into account many factors, and hence a more simple configuration has been developed as a first step in the global control of a manufacturing system. The configuration is based on cellular concept. Therefore, manufacturing cells are the bases for developing flexible manufacturing systems. In this paper, a methodology for developing flexible manufacturing cells is proposed, which integrates a series of methods and activities that characterise the implementation of manufacturing cells in typical operation systems. Also a deterministic model for batch manufacturing and part selection is proposed.